A contribuição da aplicação de sistemas de informações geográficas na elaboração dos insumos cartográficos utilizados no censo demográfico do Brasil de 2010 - Suzuki, Ricardo Teiji [UNESP] (2011)
The demographic census is the largest and most important socioeconomic research of the country since it portrays the situation closer to the reality of the population. Their result allows public policy making aimed at improving the quality of life, socioeconomic development and provides information for decision making on public and private sector. Due to the large amount of data collected, the processing of such information requires increasingly use information technology to facilitate processing. Therefore, the increasingly common use of the Geographic Information System (GIS) in various fields of knowledge contributes to the job achievement given its ability to collect, store, retrieve and view data. Following this trend, the Brazilian Institute of Geography and Statics (IBGE) also used this tool in the development of cartographic inputs, wich plays a key role for the data collection range nationwide